(untitled) (Eurasian Journal of Ecology, 2021)
Kazakhstan has significant resources for the development of ecotourism, or also known as naturebased tourism. Their nature is characterized by a high degree of environmentally rich biodiversity, flora, fauna and wildlife, with many possessing unique landscapes and ecotourism facilities. National parks in particular have the greatest potential for the development of eco-tourism, as a type of protected areas, the main task are protection of ecosystems and regulation of territorial use for ecological, educational, scientific, touristic and recreational purposes. In the academia, the study on ecotourism is dated to the early 1970’s. However, the studies on ecotourism research in Kazakhstan have emerged only in the early 2000’s and still now lacks abundant specialized research output and research interest. In light of these problems, this research paper sought to evaluate the literature on ecotourism studies in the context of Kazakhstan and discuss the main findings by prominent Kazakhstani scholars. Firstly, thorough literature review analysis of the evolution of ecotourism studies will be done. Here, we will look at its conceptual emergence; historical importance, challenges and significance for the research community; previous and current research focus; potential further research studies and the importance of studies on national parks. And secondly, the paper discusses the characteristics of ecotourism destination in Kazakhstan, the emergence of ecotourism as a scientific study among Kazakhstani scholars and its present development as well as future prospects of ecotourism studies. Our discussion and literature review will offer useful information for researchers in not only understanding the evolution of how ecotourism studies have evolved over the time in the context of Kazakhstan, but also give them a thorough overview of the current state of ecotourism industry. There is a significant research and information gap on the topic of ecotourism study in Kazakhstan and this research aims to fill that gap. Key words: Ecotourism, Kazakhstan, national parks, development, tourism.